Application of Clay and Wood Ash in Glaze Production for Ceramic Surface - Farah Nabila Nordin; Humin Jusilin; Oscar Gordon Wong (2018)
Ash glaze is not used in Sabah as a commercial glaze. Local ceramics, especially in Kota Belud and Semporna, do not know in processing and lack knowledge in the use of the formula needed in producing glaze. The purpose of this study is to identify, documentation and analyze natural materials that can produce a glaze. The method used by the researcher is a qualitative method and conducting workshop experimental activities at ceramic workshops, University Malaysia Sabah. The formula used in this research is a line blend formula by Michael Cerv (2016). This line blend formula is a combination of one and two materials to get a satin and matt effect. The researcher produced six samples using one technique in this study. The researcher found that through this study, the six samples showed shiny and flat surface. This study can provide an easy way especially the ceramic entrepreneurs in Kota Belud and Semporna to produce more quality ceramic crafts.